In Vitro Comparison of Modes of Failures among Titanium and One- and Two-piece Zirconia Abutment under Static Load - Alqahtani, Fawaz; AlAmar, Mohammed (European Journal of Dentistry, 2020)
Objectives The objective was to assess modes of failures under static load (SL) among titanium (Ti) and one- and two-piece zirconia abutment (ZA) in vitro.Materials and Methods The Ti abutments were digitally scanned for the fabrication of the one- and two-piece zirconia abutment specimens. This was done to standardize the design of the one-piece abutment and make it the blueprint of the Ti abutment. Twenty-one implant abutments and 21 implant replicas were categorized into three groups as follows: group 1 (Titanium group), group 2 (one-piece ZA group), and group 3 (two-piece ZA group). A 250K-cycle, linear fatigue-load, reaching 10 to 210 Newton (N), was put on all specimens using an all-electric dynamic test instrument and the specimens were loaded until fracture.Statistical Analysis Assessment of mode of fracture among the groups was done visually. Significance was based below 0.05.Results Screw fracture (n = 7) and abutment bending at the apical part (n = 7) occurred in the Ti group. In the one-piece zirconia group, screw and abutment fractures occurred in seven and seven cases, respectively. In the two-piece zirconia group, screw fracture (n = 7) above the Ti zirconia junction (transgingival segment) and abutment fracture (n = 7) were determined as the failure modes.Conclusion In conclusion, all abutments underwent failures under SL in vitro; and the mode of failure modes varied among the different abutment designs used.
Keywords: fracture resistance; mode of fracture; static load; titanium; zirconia